Correction: Barkjohn et al. Correction and Accuracy of PurpleAir PM2.5 Measurements for Extreme Wildfire Smoke. Sensors 2022, 22, 9669 - Karoline K. Barkjohn; Amara L. Holder; Samuel G. Frederick; Andrea L. Clements (Sensors)
In the original publication [...]